Enhanced bonding stability of Fe oxide layer on low carbon steel via low-pressure air oxidation - Jun Sang Park; Hidemi Kato; Eun-Ae Choi; Seung Zeon Han (Journal of Materials Research and Technology, 2025)
The oxidation behavior of low carbon steel (SS400) was investigated at 500 °C under different air pressures: 1 atm, 1/10,000 atm, and 1/50,000 atm. The results showed that the oxide growth rate at 1/10,000 atm was higher than at atmospheric pressure, primarily due to the reduced formation of dense Fe2O3 on the oxide surface. Oxide layers formed at 1/10,000 atm and 1/50,000 atm exhibited better adhesion to the steel substrate, as they featured larger oxide grains and increased contact area with the steel, leading to a greater number of chemical bonds at the oxide-steel interface. Although Kirkendall pores were more prominent at lower air pressures, they did not significantly affect the bonding strength between the oxide and the steel.